2015
DOI: 10.1097/jom.0000000000000482
|View full text |Cite
|
Sign up to set email alerts
|

Developing Surveillance Methodology for Agricultural and Logging Injury in New Hampshire Using Electronic Administrative Data Sets

Abstract: These data indicate that it is possible to identify agricultural and logging injury events in PCR and hospital data. Multiple data sources increase catchment; nevertheless, limitations in methods of identification of agricultural and logging injury contribute to the likely undercount of injury events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Future iterations of the WINS platform will begin integrating other data sources from the state of Wisconsin [e.g., ambulance runs based on models outlined by Scott et al ( 24 , 25 )] to capture more injuries that may have been treated outside of MCHS or not covered by SHP insurance. In addition, chart reviews will be conducted on a sample of farm-related injuries in the out-farm group, and the WINS source population will be expanded by including other healthcare systems that serve children and adolescents beyond north-central regions of Wisconsin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future iterations of the WINS platform will begin integrating other data sources from the state of Wisconsin [e.g., ambulance runs based on models outlined by Scott et al ( 24 , 25 )] to capture more injuries that may have been treated outside of MCHS or not covered by SHP insurance. In addition, chart reviews will be conducted on a sample of farm-related injuries in the out-farm group, and the WINS source population will be expanded by including other healthcare systems that serve children and adolescents beyond north-central regions of Wisconsin.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts were also made to identify recreational activities that took place in the farm location (e.g., riding horses or ATVs). Medically-attended farm-related injuries were ascertained based on adaptations of injury surveillance models outlined by Landsteiner et al ( 23 ) and Scott et al ( 24 , 25 ). Injury details were extracted from medical diagnoses observed during emergency, inpatient, urgent care, or outpatient encounters in the MCHS electronic data repository.…”
Section: Methodsmentioning
confidence: 99%
“…Unstructured data analysis is reported as challenging in EHR datasets [31] and claims databases [34], which is due to processing textual data [34] and coding the data to recognised coding formats such as the ICD, leading to potentially lower quality analysis or the need to exclude records [31,35,39]. A study found that many variables that were available for analysis, such as medication lists, education and income that were excluded from the study due to inabilities to process unstructured data [31].…”
Section: Sources Of Data For Predicting Outcomes To Wmsdsmentioning
confidence: 99%
“…A study found that many variables that were available for analysis, such as medication lists, education and income that were excluded from the study due to inabilities to process unstructured data [31]. Unstructured data also has its benefits, such as being able to capture sequence of events that can be missed from structured data [35].…”
Section: Sources Of Data For Predicting Outcomes To Wmsdsmentioning
confidence: 99%
“…National surveillance systems that apply uniform definitions and coding schemes provide value to stakeholders and facilitate collaborations between researchers nationally and internationally. 12,[14][15][16][17] Yet, gaps remain in national statistics, and support is needed to supplement current national surveillance to be more inclusive and comprehensive, recognizing the whole spectrum of agriculturerelated injury and fatality cases.…”
Section: Implications and Recommendationsmentioning
confidence: 99%